Hospital Collaboration with Emergency Medical Services in the Care of Patients with Acute Myocardial Infarction: Perspectives from Key Hospital Staff - Landman, Adam B. (2012)
OBJECTIVE: Evidence suggests that active collaboration between hospitals and emergency medical services (EMS) is significantly associated with lower acute myocardial infarction (AMI) mortality rates; however, the nature of such collaborations is not well understood. We sought to characterize views of key hospital staff regarding collaboration with EMS in the care of patients hospitalized with AMI. METHODS: We performed an exploratory analysis of qualitative data previously collected from site visits and in-depth interviews with 11 US hospitals that ranked in the top or bottom 5% of performance on 30-day risk-standardized AMI mortality rates (RSMRs) using Centers for Medicare and Medicaid Services data from 2005–2007. We selected all codes from the first analysis in which EMS was most likely to have been discussed. A multidisciplinary team analyzed the data using the constant comparative method to generate recurrent themes. RESULTS: Both higher and lower performing hospitals reported that EMS is critical to the provision of timely care for patients with AMI. However, close, collaborative relationships with EMS were more apparent in the higher performing hospitals. Higher performing hospitals demonstrated specific investment in and attention to EMS through: 1) respect for EMS as valued professionals and colleagues; 2) strong communication and coordination with EMS; and 3) active engagement of EMS in hospital AMI quality improvement efforts. CONCLUSION: Hospital staff from higher performing hospitals described broad, multifaceted strategies to support collaboration with EMS in providing AMI care. The association of these strategies with hospital performance should be tested quantitatively in a larger, representative study.